The Application of Institutional Excellence Standards in Bethlehem’s Private Schools Based on Malcolm Baldrige’s Model - Awad, Shireen Elias; Abu Samra, Mahmoud Ahmed (Journal of Educational and Psychological Sciences, 2023)
The need for institutional excellence has grown in recent decades as standards of excellence have become a necessity for administrative development to raise the level of performance. This has encouraged the adoption of excellence models, like Malcolm Baldrige's model of institutional excellence. For this, the current study examined the extent to which institutional excellence standards are applied in Bethlehem’s private schools based on Malcolm Baldrige's model. The descriptive analytical approach was used, and the population included all teachers and administrative employees in Bethlehem’s private schools for the academic year 2022/2023, there number is (860) members. The sample included (214) teachers and administrative employees who were randomly selected (cluster sample). A 42-item questionnaire was designed to collect data. The most important results revealed that the respondents' estimates of the extent to which standards of institutional excellence were applied according to Malcolm Baldrige's model recorded a high score with an average of (3.9). Thus, the study recommended promoting the implementation of standards of institutional excellence in private schools to maintain these good results and improve them.
Keywords: Institutional excellence; Malcolm Baldrige model; private schools; Bethlehem; Palestine